Job satisfaction and stress among police officers in Iceland - Viktor Freyr Hjörleifsson 1995- (2019)
The reason for this study is to see how job satisfaction and stress is within the police in Iceland. Job satisfaction is important in every job, it is important because it has an effect on employee´s mental and physical health and for example, these factors can increase the overall performance of work. Individuals can experience stress in everyday life and some jobs can have more stress related tasks than others. Police officers´ work may contain a lot of stress related tasks, especially those who have to face some difficult situations. Such situations may vary but, for example, traffic accidents where someone has passed away or when individuals simply attack an officer. This study was done with 78 police officers in Iceland, 54 males and 24 females. The study showed that age and stress were major factors affecting job satisfaction. The officers answered 41 questions about job satisfaction, stress and seven background questions. Keywords: Job satisfaction, stress, police officer, Iceland Tilgangur þessarar rannsóknar var að rannsaka starfsánægju og streitu hjá lögreglumönnum á Íslandi. Starfsánægja er mikilvæg á öllum vinnustöðum, hún er mikilvæg vegna áhrif hennar á andlega og líkamlega heilsu starfsmanna og getur aukið starfsgetu sem dæmi má nefna. Einstaklingar geta uppplifað streitu í daglegu lífi og geta sumir vinnustaðir verið með fleiri streituvaldandi þætti í starfi heldur en aðrir vinnustaðir, til dæmis að starfa sem lögreglumaður. Lögreglumenn þurfa oft að fara á vettvang þar sem upp koma erfiðar aðstæður, eins og til dæmis bílslys þar sem einstaklingar hafa látist eða þar sem er ráðist gegn lögreglumanninum og því margar aðstæður þar sem streita getur aukist. Í þessari rannsókn voru 78 lögreglumenn, 54 karlmenn og 24 kvennmenn sem tóku þátt. Niðurstöður sýndu fram á að aldur og streira hafa mikil áhrif á starfsánægju. Lögreglumennirnir svöruðu 41 spurningum um starfsánægju og streitu ásamt 7 bakgrunnsspurningum. Lykilorð: Starfsánægja, streita, lögreglumenn, Ísland